The effect of two types of cross-linking on some mechanical properties of collagen. - Thompson, J; Czernuszka, J (1995)
Samples of collagen were cross-linked by two different methods: (a) glutaraldehyde and (b) a combination of dehydrothermal treatment and cyanamide. The elastic modulus, the ultimate tensile strength (fracture stress), strain to failure, work of fracture, and fracture toughness were measured before and after cross-linking in ambient laboratory conditions, and during immersion in water. These tests were all performed over a range of strain rates. For collagen tested in the wet condition, it was found that cross-linking increased the elastic modulus from approximately 25-30 MPa, to between 55 and 60 MPa, but there was little effect on fracture stress, and strain to failure was reduced. The work of fracture of the collagen decreased on cross-linking. Cross-linking had the same effect on the elastic modulus, fracture stress, and strain to failure of dry collagen, but the work of fracture was unaffected. In conclusion, cross-linking increased the elastic modulus, reduced the strain to failure, and had little effect on the fracture stress of collagen under the present experimental conditions.